(untitled) (Damascus University Journal of agriculture sciences, 2025)
The research aimed to study the type and quantity of clay minerals for the soil of the Shin Basalt Plateau to find out the extent of soil development, which reflects the extent of its fertility and the appropriate measures to reduce its deterioration. Two samples were taken from each village, from a depth of (25-50) cm, and the study was carried out using X-ray diffraction technology. A study of the mineral composition of the soil of the region revealed the presence of the following group of clay minerals: (kaolinite - smectite - mica), the highest percentage of kaolinite mineral in the total samples, as it reached 65.5% of the amount of clay found in the village of Pershin. It was followed by the mineral smectite with a percentage between (26.1 and 53.2)%, then the mineral mica with a percentage between (5.3 and 10.5)%. When the samples were treated with glycerol vapor, the presence of the mineral montmorillonite belonging to the smectite group was revealed. When studying the mother rocks to know the chemical elements involved in their composition, it was found that they follow the basic basalt and are rich in plant nutrients that can be used when they are liberated